THE UNIQUENESS OF THE FIGHT AGAINST RUSSIAN INVADERS IN THE SHAHRISABZ REGION - Parmonov Sharofiddin Shavkatovich; Xayritdinov Otabek Murotjon o‘g‘li (The Bioscan, 2024)
This article covers the period from the 60s to the 70s of the XIX century, namely the Emir of Bukhara: the reasons for the disobedience of the Shahrisabz to the Emirate of Bukhara under Amir Muzzaffar, the incompetence of Emir Muzaffar against the Russian invasion, the Abdumalik Torah movement, The brogan struggle of Bobobek and Jorabek against the Russian invasion.